Analysis of Internal and External Factors Related to Compliance with Drug Drinking in Patients Leprosy in Kupang City - Yuliana Timu; Deviarbi Sakke Tira; Marselinus Laga Nur (Universitas Nusa Cendana, 2021)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae. Poor preventive management can lead to progressive leprosy. Kupang City is in the first place to contribute 52 cases of leprosy. Regular treatment is very important to cure leprosy. Non-adherence to taking the medication regularly results in resistance to MDT which can lead to fatal disability. This study aimed to analyze internal dan external factors related to medication adherence to leprosy patients in Kupang City in 2019. This is a cross-sectional study. Sample in this study as many as 52 people with leprosy. The analysis was performed using the Chi-Square test. Results shows knowledge (p = 0.00), family role (p = 0.033), the role of health workers (0.008), and leprosy reactions (p = 0.004) related to medication adherence. But attitude (p = 0.471) is not related to medication adherence. It is suggested to the Kupang City Health Office to collaborate with administrators of infectious disease programs, especially leprosy so that they can socialize with families and communities to motivate patients for taking medication.